Metallogenic evolution of the southern Appalachian Orogenic Belt and Mississippi Valley - Maassen, Larry W (Rhodes University, Faculty of Science, Department of Geology, 1983)
Plate tectonic theory provides logical explanations for the major tectonic events in the eastern US during Paleozoic time. The details of these tectonic events are becoming more apparent with the accumulation of new data, especially radiometric age dates. When plate tectonic theory is applied to specific tectonic events for which there is no substantial evidence, such as intracontinental hotspot rifting environments and Precambrian subduction zones, the proposed models may become very speculative. A misconception concerning the geology of the central US is that this region is structurally stable. However, geologists are currently paying considerable attention to the interlocking network of faults that in a general way follow the 38th parallel of latitude from west-central Virginia into Central Missouri (and may extend farther to the east and west). Most of the displacement along this zone occurred during the Precambrian, but different parts have moved during several periods of post-Precambrian time. In the basement the lineament may be a wide fracture zone that extends deep into the crust and is thus responsible for the magmatic iron deposits of the Southeast Missouri and may be either directly or indirectly responsible for the localization of the Mississippi Valley type deposits that occur sporadically along its length. Whether or not plate-tectonic processes operated during the Precambrian is open to speculation and the lineament may or may not be related to plate tectonic activity, but it is obvious that throughout time inherent zones of weakness are important in the localization of ore deposits. The occurrence of several major mineral districts at the intersections of the 38th parallel lineament with other major structural features, particularly in some uplifted areas and fault zone intersections, suggests that other similar structural uplifts and fault-zone intersections should be investigated for undiscovered new districts or extensions of known districts. Small uneconomic mineral occurrences along fault zones intersecting the lineament may merit further examination as they may be indications of undiscovered deposits at depth. The overall tectonic environment in the Appalachian region was an important control on the localization of massive sulfide, gold, titanium, and tungsten deposits. The deposits occur in clusters, either in Late Precambrian spreading centers and associated rift systems related to the breakup of proto-Pangea, or in Eocambrian and Devonian low-potassium tholeiitic volcanic and plutonic rocks associated with the volcanic island arc systems which developed during the closing of the Iapetus Ocean. Feiss and Hauck (1980) are confident that moderate sized (1-10 million ton) massive sulfide deposits are yet to be found at depth in these regions of the southern Appalachians, but large (greater than 20 million ton) massive sulfide deposits are unlikely to exist. The Mississippi Valley carbonate-hosted deposits of lead-zinc-baritefluorite, that occur to some extent throughout the Paleozoic section, and the Silurian "Clinton" iron ores owe their origin and distribution to normal sedimentary and diagenetic processes resulting from the transgressions of the epeiric seas. Others, such as the residual deposits of managnese iron, and aluminum, owe their existence to the afore mentioned processes, but must also have had subsequent exposure to the concentrating mechanism of weathering in a stable environment. The Mississippi Valley type occur primarily around paleo-basement highs and paleoshorelines; therefore, the formation of domes and arches within the continental interior during bathygenic episodes was a major factor controlling the localization of these deposits. These broad upwarps were preferential sites for reefal development and facies changes, and, during epeirogenic periods, these positive features have resulted in erosion and karsting of the the carbonate rocks by meteoric waters and have thus been prepared for mineralization. Deposits of this type are most common below a pre-Middle Ordovician unconformity and should be sought along major domes and arches, and along major lineaments. The association of Applachian type deposits with arches is indeterminate because a structure as subtle as an arch would be difficult to detect following overprinting by the deformation of the Alleghany orogeny; however, there is no reason to suspect that this type of positive feature did not play a role in their location. In conclusion, plate movements were a major control on the Paleozoic tectonic history of the eastern US and were also the primary control on the localization of the base metal, gold, tungsten, chromite, and titanium deposits of the southern Appalachians. However, important sedimentary and diagenetic deposits were localized primarily by arch, dome, and basin development during bathygenic episodes. Whether these submergent episodes are the result of plate motion or whether plate motion is indirectly related to submergent episodes, as suggested by Sloss and Speed (1974), remains a problem that needs to be investigated and debated further.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Metallogeny -- Appalachian Region; Metallogeny -- Mississippi River Valley; Plate tectonics -- Appalachian Region; Plate tectonics -- Mississippi River Valley